Testing the sprint curve model using the 150m Bailey-Johnson showdown - Mureika, J. R. (arXiv e-print repository, 1997)
Recently, a simple model was derived to account for a sprinter's energy loss around a curve, based on previous sprint models for linear races. This paper offers a quick test of the model's precision by comparing split times from Donovan Bailey's 150m "Challenge of Champions'' race at Skydome on June 1st, 1997. The discrepancy in the track configuration which almost prompted Bailey to drop from the race is also addressed.